Mapping careful epidemiology: Spatialities, materialities, and subjectivities in the management of animal disease. Issue 3 (14th January 2020) - Enticott, Gareth; Ward, Kim
Abstract : As a geographical tool, epidemiology represents a distinct way of seeing and knowing disease. Used as a governmental rationality to control animal disease, changes in epidemiological practice have been understood as technological evolutions. In doing so, however, this view disguises the "messy realities" of epidemiology, the relationship between different epidemiological practices, and the work required to make epidemiology "matter." Drawing on a case study of the management of bovine tuberculosis in England and Wales, the paper examines how epidemiological practices are developed, replaced, and contested. By focusing on practices of epidemiological record keeping and mapping, the paper argues that epidemiology arranges different spatialities, materialities, and subjectivities in order to enact the presence of animal disease. The paper tracks changes to these arrangements over time, showing how they seek to redefine the appropriate people, places, and practices that allow disease to be seen. In doing so, however, the paper shows how versions of epidemiology deposit "residues of practice" that influence how new epidemiological arrangements are received and negotiated in use. A central theme to these negotiations is an attempt to accommodate complexity by employing a caring and/or careful approach to epidemiology, as revealed through the practices of "re‐recording" and "re‐mapping." Whilst this demonstrates the contextual and in‐situ nature of epidemiology, highlighting the contribution of a caring/careful epidemiology also serves to make these practices relevant for future iterations of epidemiological practice by making them "matter."